Prudence and prevention – empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics Letters)

The gambler’s and hot-hand fallacies: Empirical evidence from trading data - Pelster, Matthias (Economics Letters)

Secular stagnation? Is there statistical evidence of an unprecedented, systematic decline in growth? - Fritz, Marlon; Gries, Thomas; Feng, Yuanhua (Economics Letters)

Culture and the disposition effect - Breitmayer, Bastian; Hasso, Tim; Pelster, Matthias (Economics Letters)

Are cryptocurrency traders pioneers or just risk-seekers? evidence from brokerage accounts - Pelster, Matthias; Breitmayer, Bastian; Hasso, Tim (Economics Letters)
Are cryptocurrency traders driven by a desire to invest in a new asset class to diversify their portfolio or are they merely seeking to increase their levels of risk? To answer this question, we use individual-level brokerage data and study their behavior in stock trading around the time they engage in their first cryptocurrency trade. We find that when engaging in cryptocurrency trading investors simultaneously increase their risk-seeking behavior in stock trading as they increase their trading intensity and use of leverage. The increase in risk-seeking in stocks is particularly pronounced when volatility in cryptocurrency returns is low, suggesting that their overall behavior is driven by excitement-seeking.
Keywords: cryptocurrencies; bitcoin; investor; risk-seeking

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)

Tax neutrality under irreversibility and risk aversion - Niemann, Rainer; Sureth-Sloane, Caren (Economics Letters)